ANALYSIS OF UINSU FEMALE STUDENTS' PREFERENCES FOR LIPSTICK SELECTION USING THE CHI SQUARE TEST - Putri Oktavia, Ade; Prasetyo, Dimas; Syifa Gultom, Fairus; Ritonga, Fatimah; Ardena Br Ginting, Nike; Taulia Br Tarigan, Sabrina (Pena Cendekia Insani, 2023)
This study aims to identify and analyze the factors that influence the preferences of female students of the State Islamic University of North Sumatra (UINSU) in choosing lipstick products that took place from 28 to 30 October 2024. The factors studied include the attributes of color, aroma, type of lipstick, price, and brand. This research uses quantitative methods with a comparative causal approach and chi-square analysis. Primary data is obtained from data collected directly from respondents through surveys using questionnaires. And secondary data is obtained from information on previous research reports, books, academic journals, and official documents. Research results show the decision to buy lipstick, from highest to lowest is color with 14.84, type 12.6655, brand 10.4346, aroma 8.7185, and price 12.2059. when viewed from the order, the higher the Ao value, the quality of the lipstick is at the top of the list that is most concerned by the respondent, and so on. Therefore, table 4.9 shows that rank 1 is color, rank 2 is type, rank 3 is aroma, rank 4 is brand and the last rank is the aroma of lipstick.